Dampak Sosial Kekerasan Dalam Rumah Tangga Terhadap Anak di Kabupaten Bantaeng - Yuniar, Jusfira; Mukramin, Sam'un; Haniah, St; Ismail, Lukman (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to further examine what social impacts are experienced by a child who is a victim of Domestic Violence (KDRT) and to provide equal attention to children as the nation's shoots and is expected to be able to suppress acts of violence which continue to increase every year. This research uses a qualitative method with the type of case study research, namely research on natural object conditions where the researcher is a key instrument, data collection techniques are carried out in a triangulation (combined) manner, data analysis is inductive, qualitative research data emphasizes meaning rather than generalization. The results of the study show that domestic violence greatly affects children's character education. Because children learn and imitate and gain knowledge about the use of violence in solving problems. Children can learn and imitate from acts of violence committed by fathers to mothers, and peers, teachers / lecturers against him.